2019
DOI: 10.1016/j.molcel.2019.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Elongation Factor TFIIS Prevents Transcription Stress and R-Loop Accumulation to Maintain Genome Stability

Abstract: SummaryAlthough correlations between RNA polymerase II (RNAPII) transcription stress, R-loops, and genome instability have been established, the mechanisms underlying these connections remain poorly understood. Here, we used a mutant version of the transcription elongation factor TFIIS (TFIISmut), aiming to specifically induce increased levels of RNAPII pausing, arrest, and/or backtracking in human cells. Indeed, TFIISmut expression results in slower elongation rates, relative depletion of polymerases from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 64 publications
3
84
1
Order By: Relevance
“…If these roadblocks are not resolved, collisions with the replication machinery will lead to replication fork breakdown and DNA strand breaks. Important factors have been identified that prevent and resolve R-loops, including the RNAPII activator CDK9 and the RNA:DNA hybrid endonuclease RNase H1 [27][28][29][30][31][32][33][34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…If these roadblocks are not resolved, collisions with the replication machinery will lead to replication fork breakdown and DNA strand breaks. Important factors have been identified that prevent and resolve R-loops, including the RNAPII activator CDK9 and the RNA:DNA hybrid endonuclease RNase H1 [27][28][29][30][31][32][33][34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…We found additional proteins described to bind to R-loops (99) and prevent their formation (100) in the BioID dataset. These include members of the spliceosome (101,102), the exosome (103), topoisomerase 1 (104) and an associated bromodomain-containing protein BRD2 (105), transcription elongation factor TFIIS (106) or FACT (107). These proteins are involved in the resolution of genome maintenance conflicts caused by R-loop formation in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of either RNase H, SETX or EXOSC10 results in increased levels of DNA:RNA hybrids and genomic instability, as described above, [ 29,49,54,63,64 ] which suggests that both RNase H and the SETX‐exosome system are required to prevent the accumulation of DNA:RNA hybrids in the DNA. However, the reason why both nucleolytic systems are needed is not understood yet.…”
Section: Resolution Of Dna:rna Hybrids At Dsbsmentioning
confidence: 94%
“…[ 51 ] However, R‐loops can cause genome instability and, during transcription, RNA binding proteins and processing factors assemble with the nascent RNA and prevent R‐loop formation. [ 44,52–55 ]…”
Section: Dilncrnas Produced At Dsbs Engage In Dna:rna Hybrid Formationmentioning
confidence: 99%